Pengaruh PMR (Progressive Muscle Relaxation) Terhadap Insomnia pada Lansia di Panti Sosial Lanjut Usia Tresna Werdha Natar Provinsi Lampung Tahun 2012 - Thahir, Andi (Universitas Islam Negeri Raden Intan Lampung, 2015)
Sleep disturbance is also known as a significant cause of morbidity. There are some serious effects on sleep disturbance in the elderly. Based on the results of a preliminary study conducted by researchers at the beginning of March 2012 at Tresna Werdha Natar Elderly Social Institution, it was found that there were 103 elderly people who actively participated in health screening activities, 78 of whom had insomnia. The purpose of this study was to determine the effect of PMR (Progressive Muscle Relaxation) on insomnia in the elderly at Tresna Werdha Natar Elderly Social Institution in Lampung Province in 2012. The research method used was quasi-experimental with the Pre Post Test Control Group approach. The sample population taken in this study is 50 respondents divided into two groups, namely intervention and control. This study uses t-test analysis (paired t test) to measure the condition of insomnia before and after PMR and independent t-test to see differences between the intervention and control groups. This research was conducted on June 6-13 using a questionnaire and observation sheet. The results of this study are the level of insomnia before the elderly get progressive muscle relaxation, which is an average of 7.80. The level of insomnia after the elderly get progressive muscle relaxation is an average of 6.40. There is a difference in insomnia between before and after the elderly get progressive muscle relaxation, which is an average of 1.40. There is an influence of PMR (Progressive Muscle Relaxation) effect on insomnia in the elderly in social care institutions Tresna Werdha Natar Lampung Province with P Value 0,000 with a confidence level of 0.05 so that P Value <α (0,000 <0.05).